2020
DOI: 10.3390/jcm9092767
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Obesity—Cumulative or Complementary Effects On Adipokines, Inflammation, and Insulin Resistance

Abstract: Background: Diabetes and obesity are increasingly significant public health issues. The aim of this study was to evaluate the relationship between adipocytokines (leptin, ghrelin, and chemerin), inflammation (sVCAM1—soluble vascular adhesion molecule 1, sICAM1—soluble intercellular adhesion molecule 1), and insulin resistance in the presence of obesity and diabetes mellitus. Methods: 88 subjects, with a mean age of 61.96 ± 10.15 years, 75% of whom were women, were evaluated (in order to consider different asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
(179 reference statements)
2
7
0
1
Order By: Relevance
“…Different mechanisms are responsible, including the fact that chronic high leptin level leads to leptin insensitivity [ 57 ]. Our results are in line with previous ones [ 11 , 17 , 18 , 22 , 28 , 55 , 58 , 59 , 60 , 61 , 62 ], showing higher levels in obese or diabetic patients and a positive correlation with body mass index (as reported in [ 15 , 28 ]).…”
Section: Discussionsupporting
confidence: 93%
“…Different mechanisms are responsible, including the fact that chronic high leptin level leads to leptin insensitivity [ 57 ]. Our results are in line with previous ones [ 11 , 17 , 18 , 22 , 28 , 55 , 58 , 59 , 60 , 61 , 62 ], showing higher levels in obese or diabetic patients and a positive correlation with body mass index (as reported in [ 15 , 28 ]).…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed significant positive correlation between chemerin level and hsCRP while there was significant negative correlation between omentin-1 and both chemerin and hsCRP in CAD with and without type 2 diabetic patients. Similar findings were reported previously in metabolic syndrome (11,13,33,34) .…”
Section: Discussionsupporting
confidence: 92%
“…It suggests that adipocytokines are involved in the inflammatory response, which directly promotes the occurrence of CAD. Adipose tissue secretes many adipokines including adiponectin, chemerin, omentin-1, leptin, resistin, retinol binding protein 4, tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) (3,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In adipose tissues, chemerin is widely distributed and displays endocrine activity, with signi cant correlation in metabolic diseases such as obesity, type 2 diabetes, and cardiovascular disease. [11][12][13] Chemerin levels in synovial uid have been found to correlate with OA severity using the Kellgren-Lawrence grade as a criterion. 14 Furthermore, ChemR23 is expressed in articular synoviocytes, 15 and its expression is associated with the production of a variety of in ammatory mediators that are released in synovial lesions in OA and affect articular cartilage.…”
Section: Introductionmentioning
confidence: 99%